2014
DOI: 10.1159/000360483
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Patients with Pathological Tumor Stage T3 Urothelial Carcinoma of the Bladder following Radical Cystectomy in a Single-Center Series with 116 Patients

Abstract: Objective: Outcome prediction of pT3 urothelial carcinoma of the bladder (UCB) after radical cystectomy (RC) remains challenging. The objective of our study was to determine high-risk patients with poor survival outcome in a heterogeneous group substaged pT3 who might profit from early adjuvant chemotherapy. Materials and Methods: We compiled clinicopathological and immunohistochemical data of E-cadherin (E-cad) expression in 116 patients with pT3 UCB after RC in our single-center series. Multivariable Cox reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Taken together, the data suggest that - if managed by radical cystectomy - women with invasive bladder cancer have a similar survival as men if matched according to the tumour stage [18]. In non-stage-matched cohorts, the poorer survival of women is most likely driven by the more advanced stages in women.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the data suggest that - if managed by radical cystectomy - women with invasive bladder cancer have a similar survival as men if matched according to the tumour stage [18]. In non-stage-matched cohorts, the poorer survival of women is most likely driven by the more advanced stages in women.…”
Section: Discussionmentioning
confidence: 99%
“…Stage, grade and nodal status are proved as the most significant predictors of OS with hazard ratio exceeding 2 [ 9 ]. Other potential factors include: neoadjuvant chemotherapy [ 9 ], smoking habits [ 9 ], general condition status [ 10 ], age [ 11 ], American Society of Anesthesiologists score [ 12 ], Eastern Cooperative Oncology Group score, Elixhauser index [ 13 ] or delay time from first symptoms to surgery [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, only 14% were considered significantly defined as extraprostatic disease and/or pathological Gleason score ≥ 7. Previous investigators reported incidental PCa involvement in BCa patients treated with RCP of 3-50% [11][12][13][14][15][16][17] . Interestingly, we recorded an increasing rate of PCa over the years.…”
Section: Discussionmentioning
confidence: 97%